Implementasi e-Government pada Layanan Informasi Publik Berbasis Website Smart Desa Digital di Desa Tegal Angus Kecamatan Teluknaga - Muhamad Nur Adillah; Ahmad Murodi; Yudi Muhtadi (Universitas 17 Agustus 1945, 2024)
The purpose of this research is to determine the implementation of e-government in public information services through the digital village smart website, the factors that become obstacles, and efforts to overcome these obstacle factors in order to improve public information services through the digital village smart website in Tegal Angus Village. . Researchers use Edward III's theory in Subarsono, 2011:90-92 with four indicators, namely; 1) Communication; 2) Resources; 3) Disposition; and 4) Bureaucratic structure, with descriptive qualitative research methods. The results of this research are that communication is considered effective with the village government by conducting outreach. However, human and non-human resources, such as the quality of human resources, internet access, and educational background, are still the main obstacles. Efforts to overcome these obstacles include digital technology training, outreach via social media, direct technical assistance, and promotions by community leaders.